Updating the knowledge of the flower flies (Diptera: Syrphidae) from Chile: Illustrated catalog, extinction risk and biological notes - Barahona-Segovia, Rodrigo M.; Riera, Pamela; Pañinao-Monsálvez, Laura; Guzmán, Vicente Valdés; Henríquez-Piskulich, Patricia (Zootaxa, 2021)
Syrphidae, more commonly known as flower flies, are considered one of the most important Diptera families worldwide because of their critical role in pollination, biological control and decomposition of organic matter. The study of these flies in Chile has stagnated due to a lack of local experts as well as the absence of an updated catalog of species. This study is an attempt to remedy the latter of these issues by providing an illustrated and updated catalog to the Syrphidae of Chile. Species are presented under currently accepted names, with synonyms and previous combinations listed and original references. Type localities, world and Chilean distribution by geopolitical Chilean regions, taxonomic and biological notes, a complete record of bibliographic references and extinction risk under IUCN Red List criteria are provided. This catalog recognizes 132 species of Syrphidae, belonging to four subfamilies (Eristalinae, Microdontinae, Pipizinae and Syrphinae), 13 tribes and 47 genera. A total of 46 species (34.84 %) is restricted to the geopolitical territory of Chile. Eight species are considered exotic, one is considered incertae sedis and three are based on doubtful records. Seventeen species of 10 different genera (Copestylum Macquart, 1846; Dolichogyna Macquart, 1842; Eosalpingogaster Hull, 1949b; Eupeodes Osten Sacken, 1877; Meromacrus Rondani, 1848; Palpada Macquart, 1834; Paragus Latreille, 1804; Sphiximorpha Rondani, 1850; Sterphus Philippi, 1865 and Toxomerus Macquart, 1855) are reported from Chile for the first time. A total of 44 species (33.33 %) reported from Chile are directly threatened by human activities such as agriculture, forestry, mining and/or urbanization and indirectly by climate change. The gaps found in the geographic distribution of Chilean flower fly species and what it means for its use by disciplines such as ecology, floral biology and agronomy, are discussed. In addition, the use of this illustrated catalog for biological conservation, the potential definition of priority areas and ecosystem management plans based on this group of Diptera are also discussed.